2009
DOI: 10.24135/pjr.v15i2.982
|View full text |Cite
|
Sign up to set email alerts
|

Covering the environmental issues and global warming in Delta land: A study of three newspapers

Abstract: This article explores the coverage of environmental issues in the daily newspapers of Bangladesh, a South-Asian country facing the onslaught of global warming because of its low-lying deltaic plains and overpopulation. The results are based on an examination of the content of environmental coverage in three national daily newspapers (two Bangla and one English-language) during June 2007. Drawing on field theory and analytical frames from journalism studies, this study examines the principles of journalistic pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
7
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 12 publications
(12 reference statements)
2
7
0
Order By: Relevance
“…Additionally, positive corporate media coverage reduces corporate risk and minimizes social threats [72]. Das et al [74] have described how Bangladeshi media are concerned about social and environmental issues regarding corruption and government irregularities regarding corporation and this argument is supported by Islam and Islam [75]. We believe that the Bangladeshi media explicitly and implicitly reports on corporate corruption, which escalates corporate corruption disclosure levels.…”
Section: Corporate Media Visibility and Ccdmentioning
confidence: 88%
“…Additionally, positive corporate media coverage reduces corporate risk and minimizes social threats [72]. Das et al [74] have described how Bangladeshi media are concerned about social and environmental issues regarding corruption and government irregularities regarding corporation and this argument is supported by Islam and Islam [75]. We believe that the Bangladeshi media explicitly and implicitly reports on corporate corruption, which escalates corporate corruption disclosure levels.…”
Section: Corporate Media Visibility and Ccdmentioning
confidence: 88%
“…Bacon, Das, and Zaman (2009) found that environmental reporting in Bangladesh as a developing beat which concerned with the political, economic, and social aspects of the environment. Reza (2010) concluded that Bangladeshi newspapers concentrated on global climate change issues, impacts, and debates.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The Bearing Witness project has also related well to a journalism-as-research strategy (Bacon, 2012;Das et al, 2010;Nash, 2015, Nash, 2017) and a 'bottom up' approach with marginalised groups (Harris, 2014). Nash, for example, analyses 'silences and absences' as the norm for 'those not in a position to exercise power in the world of journalism', which are often present in conflicts of interpretation (2017, p. 147).…”
Section: Rationale and Methodologymentioning
confidence: 99%